Gellan gum and polyvinylpyrrolidone (PVP) as binding agents in extrusion/spheronization pellet formulations - Barbosa Eduardo José; Ferraz Humberto Gomes (Acta Pharmaceutica)
The aim of this work was to evaluate gellan gum as binder in pellet formulations, with theophylline as the model drug, in comparison with polyvinylpyrrolidone (PVP). A full 32 factorial design was realized, with binder and diluent factors at three levels each. Pellets were produced by the extrusion/spheronization technique, and dried in a fluid-ized bed. Physical tests and dissolution tests were conducted. The results showed that the binder factor was not significant for pellet size and granulometry distribution. Rather, trends of a different response of gellan gum were identified, in comparison with PVP, in aspect ratio and dissolution tests: more round pellets were obtained in formulations with gellan gum, and more variable dissolution resulted when this polysaccharide was present. Therefore, if the usage of this compound in immediate release pellet formulations is verified, this justifies the interest in the development of sustained release systems using gellan gum.